2017
DOI: 10.19082/4669
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting intent to immigration among Iranian health workers in 2016

Abstract: BackgroundLoss of human resources in the health sector through migration has caused many problems in the delivery of healthcare services in developing countries.ObjectiveThe aim of this study was to determine factors influencing intention to migrate in skilled human resources in Iran’s healthcare sector.MethodsThis cross-sectional study was carried out in 2016 in Iran. The study population included health sector human resources at the Tehran and Iran University of Medical Sciences. Using multi-stage cluster sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 29 publications
1
37
3
1
Order By: Relevance
“…Among other results of this study was the link between work experience, employment status and nurses' intention to immigration, so that nurses with low work experience and non-permanent employment status had more intention to immigration. The results of this study are consistent with the study of Asadi et al (2017) that was conducted on healthcare professionals in Iran (Asadi et al, 2017). This result may be related to job security, which is higher in permanently employed nurses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among other results of this study was the link between work experience, employment status and nurses' intention to immigration, so that nurses with low work experience and non-permanent employment status had more intention to immigration. The results of this study are consistent with the study of Asadi et al (2017) that was conducted on healthcare professionals in Iran (Asadi et al, 2017). This result may be related to job security, which is higher in permanently employed nurses.…”
Section: Discussionsupporting
confidence: 90%
“…The study of intention to immigration in nursing students in South Korea showed similar results (Lee and Moon, 2013;Lee, 2016). Asadi et al found similar results in determining the intention to immigration and its reasons among Iranian healthcare professionals (Asadi et al, 2017). While the Freeman's study (2012) showed that 85% of nursing graduates in a city in Canada preferred to work in Canada, and only 15% of them intended to immigrate to other countries (Freeman et al, 2012).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In Iran, the most talented students are chosen to attend medical schools. Asadi et al (3) reported that the frequency of immigration among Iranian health professionals is 54.77%, even though students are bond to upon graduation serve in medical professions at least equal to the length of their medical course. Few developed countries, such as Australia, Japan, Canada, and Germany (4), have implemented such regulations for medical education.…”
Section: Introductionmentioning
confidence: 99%
“…attention to the issues of physicians, such as continuous education, creating employment opportunities, job security, and welfare. While, in developing countries, a host of scientific, economical, technological, and political problems as well as lack of advanced research facilities, welfare, and the inability of the community to use physicians' expertise, stimulates the physicians to leave their homeland (3,5). For example, in Pakistan, low salaries and benefits, poor quality of education, job dissatisfaction, lifestyle, lack of job opportunities, working environment problems, terrorism, social harassment, management weakness, colleagues' pressure, long hours of work, and religious and political variables are the main barriers for retention of physicians (6,7).…”
Section: Introductionmentioning
confidence: 99%